Examining Structure in Scientific Research Articles: A Study of Thematic Progression and Thematic Density. (July 2018) - Leong, Alvin Ping; Toh, Audrey Lin Lin; Chin, Soo Fun
While scholars in the field of writing studies have examined scientific writing from multiple perspectives, interest in its thematic structure has been modest. Recent studies suggest that the themes in scientific writing tend to be anchored on one or a few points of departure. There has also been an attempt at quantification using the thematic-density index (TDI), although this has only been tested on abstracts. In this study, we investigated the thematic structure and TDIs of 30 research articles in biology. The results revealed a progressive thematic pattern in the introduction section, followed by an anchored development in the subsequent sections. The anchoring was realized by the pervasive use of the first-person pronoun "we." The mean TDI was lowest in the introduction section (2.593) and highest in the results section (7.095). The results were consistent across the articles in the corpus, underscoring the uniform way in which the articles were thematically structured, and in turn suggesting a core thematic pattern for scientific research writing in general. Based on these findings, the authors suggest that future studies compare the thematic structure of the introduction section vis-à-vis the other sections, and investigate the possible factors resulting in such a structure.